The Brick Mule - Michael Brown (Journal of Anthropological Films, 2023)
This observational anthrozoological ethnographic film documents the lives of Nepal's working mules. The film finds a closeness with the mules; their sale in India, their journey to Nepal and their work in the huge brick factories of the Kathmandu valley and portering goods into the high Himalayas. Stunning cinematography and a crafted soundscape paint a moving portrait of Nepal's brick mules and the people who make their living with them. Honest, but non-judgemental, the film gives a unique insight into hardship of life for people and equines alike. Yet underlying questions about humanity and our relationship with animals underpin the film.